2012
DOI: 10.1007/s11095-012-0762-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Rotigotine-Loaded Microspheres and Their Combination Use with L-DOPA to Modify Dyskinesias in 6-OHDA-Lesioned Rats

Abstract: RoMS could supply an alternative of CDS for the treatment of PD and the study indicates a potential advantage of RoMS for the treatment of mild and advanced PD patient in combination with L-DOPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…They are thus good candidates for being formulated in DDS. With this aim, Wang et al, [22] developed rotigotine loaded PLGA MP (Ro-MP) for the continuous release of this D1/D2/D3 DA agonist.…”
Section: Dds For Agonist Deliverymentioning
confidence: 99%
“…They are thus good candidates for being formulated in DDS. With this aim, Wang et al, [22] developed rotigotine loaded PLGA MP (Ro-MP) for the continuous release of this D1/D2/D3 DA agonist.…”
Section: Dds For Agonist Deliverymentioning
confidence: 99%
“…This statement is supported by data generated from a functional miRNA screening platform that indicate that only 60% of the miRNome is functional in cells [123]. Furthermore, miRNAs are also dynamically regulated, spatially and temporally regulated in animal development [109, 124] but also during development of chronic diseases [125]. Underestimating these miRNA features might result in delivery of inappropriately dosed miRNA therapeutics in targeted tissues as well as inappropriate time point for drug administration.…”
Section: Discussionmentioning
confidence: 98%
“…This abnormality causes muscular atrophy, weakness and cognitive disturbances [107, 108]. Studies demonstrated that pharmacological drugs [109], plasmid DNA-PEI complexes [110] and viral vectors [111-113] injected intramuscularly can be transported from the muscles into the brain. Myiazaki et al .…”
Section: State Of the Art Of Current Experi-
Mental Research On MImentioning
confidence: 99%
“…These are not without their side effects (many similar to l-DOPA treatment) and research groups are also investigating the use PLGA based microscale carriers as a means of sustained release of agonists such as apomorphine [194] or delivery of rotigotine [195,196] to the brain. Wang et al, were able to show that rotigotine loaded PLGA microspheres administered in conjunction with l-DOPA, reduced the abnormal involuntary movements (dyskinesias) associated with l-DOPA therapy compared to the control group (l-DOPA alone) in the 6-OHDA rat model of PD [195]. These preclinical studies, showing the ability of PLGA micro/nanoparticles to deliver therapeutic agents to the animal brain, could mean that a fundamental change in the way PD drugs are administered might not be too far from reality.…”
Section: Polymers As Drug Carriersmentioning
confidence: 99%
“…The combination of microsphere and pulsatile l-DOPA delivery produced no better therapeutic benefit than mono l-DOPA administration but significantly decreased dyskinesia (2012) [195] PLGA microspheres Rasagiline mesylate (RM) intraperitoneal Rotenone rat model RM administered via microspheres resulted in no additional therapeutic than RM in saline, but allowed administration every two weeks (2012) [196] PLGA microspheres Rotigotine intramuscular…”
Section: Polymeric Gene Vectorsmentioning
confidence: 99%